การคำนวณการแปรผันหลักมูลทางโคจรของดาวเคราะห์น้อยที่ถูกรบกวนโดยดาวพฤหัสบดีและดาวเสาร์โดยวิธีเองเก - สุนทรี พงศ์รักธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this thesis is to determine the orbital element variation of Thule asteroid by Encke method. Since the ratio of orbital period of Jupiter to that of Thule asteroid is 3:4, Thule asteroid is regularly perturbed from elliptical orbit by gravitational forces exerted on it by Jupiter resulting in the variations in time of its orbital elements. In this thesis, we calculate the variation of Thule asteroid’s orbital element caused by the perturbation form Jupiter and Saturn over the periods of 50 years, 150 years and 400 years. It is found that the resulting variations exhibit a big jump every 35.3 years which is equal to the reudevouz period of Thule asteroid and Jupiter. It is also found that the variation of the semimajor axis (a) is periodic with the period equal to 173.92 years.